Logistics & Trade Finance in ZXY International: Payment Terms in Bangladesh RMG - Hasan, Md. Mahamudul (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2021.